A study to assess the awareness regarding occupational health hazards among the employees in the laundry department of a selected hospital - Merlin Manuel; Lourdes Daphnie; Sweta D'cunha; Sucharitha Suresh (Wolters Kluwer Medknow Publications, 2015)
Background: The importance of a clean environment and linen for optimal patient care has been stressed upon since the very inception of hospitals. Individuals who work in a laundry are required to be adequately informed about the physical and health hazards present in the laundry, the known risks, and what to do if an accident occurs. Every laundry worker must be trained to know the location and proper use of the available personal protective clothing and equipment. Therefore, safe environment in the laundry is essential to maintain their health, and awareness programs should be conducted. Objective of the Study: To assess the awareness regarding occupational health hazards among the employees in the Laundry Department. Materials and Methods: The research method adopted in this study is of a descriptive type. The study was conducted in the Laundry Department of the selected hospital. The sample consisted of 15 respondents. All the employees in the department were included. The tools used to collect the data were an informal interview and the check-list and observation methods. The collected data was analyzed by percentage. Result: The study reveals that a majority of the respondents were knowledgeable about the occupational health hazards and safety measures. However, very few of them were aware of the types of occupational hazards. Conclusion: Awareness of occupational health and safety among the employees is important in the laundry area; therefore, planned orientation, training programs, and proper guidance to the employees will help reduce any kind of danger involved in the job and adoption of the necessary safety measures.